INSULTS ON SOCIAL MEDIA AS A FORM OF DIGITAL COMMUNI-CATION IMPOLITENESS: A CASE STUDY OF INSULTS IN COVID-19 PANDEMIC - Arianto, Ahmad Khoironi; Djatmika, NFN; Santosa, Riyadi (Widyaparwa, 2023)
Communication through online media has increased during the Covid-19 era. This was done to reduce face-to-face interactions to inhibit the potential spread of Covid-19. However, on the other hand, this condition also increases the potential for insulting communication on social media. This article aims to explain the forms, types, and causes of impoliteness in utterances on social media regarding Covid-19. This research is descriptive qualitative. The data used is utterances containing insults about the Covid-19 pandemic on social media. Data comes from social media, such as Instagram, Facebook, Twitter, WhatsApp and Youtube. This article uses an observation approach and record method to collect data. Furthermore, the collected data was analyzed based on three things, 1) the Indonesian Criminal Code (KUHP) to formulate forms of insults, 2) pragmatic politeness theory to see the types of communication violations that result in insults, and 3) cultural themes to explore the factors that cause someone to commit insults. The results of this study are that 1) insults can be classified into 2 categories, slander, and insults, while criticism is an opinion for progress; 2) types of politeness violations in interactions on social media fulfill the 6 elements of the politeness category initiated by Leech; and 3) the cause of humiliation is not only because of hatred but also the humiliation factor that is based on sensation. Komunikasi melalui media daring semakin meningkat di masa covid-19. Hal itu dilakukan untuk mengurangi interaksi tatap muka sehingga menghambat potensi penyebaran Covid-19. Namun, di sisi lain, kondisi itu juga meningkatkan potensi komunikasi penghinaan di media sosial. Artikel ini bertujuan untuk menjelaskan bentuk, jenis, dan penyebab ketidaksopanan dalam ujaran di media sosial seputar Covid-19. Penelitian ini bersifat deskriptif kualitatif. Data yang digunakan ialah tuturan yang mengandung penghinaan seputar pandemi covid-19 di media sosial. Data berasal dari media sosial, seperti Instagram, Facebook, Twitter, WhatsApp, dan Youtube. Artikel ini menggunakan pendekatan observasi dan metode catat untuk mengumpulkan data. Selanjutnya, data yang terkumpul tersebut dianalisis berdasarkan pada tiga hal, yaitu 1) Kitab Undang-Undang Hukum Pidana (KUHP) Indonesia untuk merumuskan bentuk penghinaan, 2) teori kesantunan pragmatik untuk melihat jenis pelanggaran komunikasi yang mengakibatkan penghinaan, dan 3) tema budaya guna menelusuri faktor-faktor penyebab seseorang melakukan penghinaan. Hasil dari penelitian ini ialah bahwa 1) bentuk penghinaan dapat diklasifikasikan ke dalam 2 kategori, yaitu fitnah dan penghinaan, sedangkan kritik adalah pendapat untuk kemajuan; 2) jenis pelanggaran kesantunan dalam interaksi di media social memenuhi 6 unsur kategori kesantunan yang digagas Leech; dan 3) penyebab penghinaan tidak hanya karena kebencian, tetapi juga muncul faktor penghinaan yang berdasarkan pada sensasi.